Keroncong : The Creativity Process of Pesona Gabuse Music Group in Pati Regency - Wismandanu, Hanur; Wadiyo, Wadiyo; Utomo, Udi (Universitas Negeri Semarang, 2019)
The Keroncong Pesona Gabuse Group is one group that uses the Keroncong genre in every performance. To maintain its existence, Pesona Gabuse always presents new and contemporary works in every performance. This research analyzes the process of creativity in realizing new works as an effort to preserve keroncong music in the country. Thus the purpose of this study is to analyze how the processes of artists in creativity, especially the personnel of the Pesona Gabuse group, using qualitative research methods. Data collection techniques using observation techniques, interviews, and document studies. The data validity technique is by using data and source triangulation, while the data analysis procedure is by data reduction, data presentation, and drawing conclusions. The theory used to analyze the data that is the theory of Creativity according to Utami Munandar. It is defined into four types of dimensions as